Gender Disparities in Their Effects on Characteristics and Prognostics of Lung Cancer Patients in Pulmonary Ward of Dr. M Djamil Hospital, Padang - Sabrina Ermayanti; Afriani Afriani; Sari Nikmawati; Russilawati Russilawati; Irvan Medison; Suyastri Suyastri (Jurnal Respirologi Indonesia, 2021)
Background: Lung cancer incidence in female tends to increase in many countries. Various studies have reported the characteristics of lung cancer in female are different from male. The purpose of this study was to determine the effect of gender on characteristics of lung cancer at Dr. M Djamil Hospital, Padang.Methods: A retrospective analytic study of lung cancer patients treated in the Pulmonary Ward of Dr. M. Djamil Hospital Padang from January 1, 2004 to December 31, 2017, with recognized cancer cell types. Data were grouped according to gender.Results: This study found that 451 lung cancer patients, male-dominant 77.8%. Female were younger than male (52.97 ± 12.79 years vs. 57.81 ± 11.23 years; p = 0.00). Most of male (94.5%) were smokers and former smokers, while 93.9% of female were non-smokers (p = 0.00). Most female were having prior history of tuberculosis (TB) (21.2% vs 11.0%; p = 0.008) and also prior history of other organs cancer (10.1% vs 3.4%; p = 0.007) than in male. Squamous cells were highest in males (41.1%), while females had adenocarcinoma (55.0%); with p = 0.008. Advanced stage in female more than male (91.8% vs 82.7%; p = 0.027). The mean life expectancy of female was longer than male, respectively 8.74 ± 1.56 and 7.29 ± 0.64 months; (p = 0.95).  Conclusion: There are differences in the epidemiology of lung cancer between male and female in Dr. M. Djamil Hospital Padang in the form of age, cell type and staging. Non-smokers, a previous history of TB and a history of cancer in other organs were more dominant in female.